Dampak Jejaring Sosial Terhadap Akhlak Anak - Mauila Sinaga; Hasan Matsum; Makmur Syukri (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This research was conducted at Al-Washliyah Teluk Nibung Tanjungbalai Private Islamic High School. This study aims to determine the Impact of Social Media on Students' Morals Towards Peers at Al-Washliyah Teluk Nibung Tanjungbalai Private Islamic High School. This type of research is qualitative research with a phenomenological approach. Data collection in this study through observation, interviews and document studies. The information collected was analyzed through data reduction, data presentation and data verification. This study used 1 Akidah Akhlak teacher, the principal and students. Based on the results of this study, it shows that the morals of students at Al-Washliyah Teluk Nibung Tanjungbalai Private Islamic High School are some that are bad, namely using cellphones during learning, wearing trendy clothes that do not reflect the way madrasah students dress. There are some that are good, namely honest and disciplined behavior practiced by some students. The impact of social media on students' morals towards peers is that they waste a lot of time because they are busy playing social media, forgetting study time, procrastinating on assignments and not caring about the people around them.